Penggunaan inovasi dgdocspace dalam pengurusan fail peribadi secara digital: kajian kes di Majlis Perbandaran Port Dickson (MPPD) (The use of dgdocspace in personal file management: a case study at Majlis Perbandaran Port Dickson (MPPD) / Rafidah Kamarudin ... [et al.] - Kamarudin, Rafidah; Abd Jamil @ Kamarudzzaman, Azura; Mohammad, Albakri; Osman, Norlis; Mohd Isnani, Zaidatulhusna (Universiti Teknologi MARA, 2020)
Hari Bertemu Pelanggan (HBP) is an essential event of the Port Dickson Municipal Council (MPPD) which is held twice a year for staff to review their Personal Files. The problem faced by the staff at the Human Resource Department (JPSM) MPPD is to handle staff Personal Files from the file room to the HBP location during the event. Risks such as loss and damage of Personal Files and the high cost in transferring staff Personal Files lead to the development of innovation known as dgDocSPACE. The implementation of the innovation has successfully reduced the operating cost, increased productivity, shortened time for reviewing Personal Files and increased customer satisfaction.